2008
DOI: 10.3390/medicina44110108
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical hernia: Factors indicative of recurrence

Abstract: Summary. Umbilical hernia has gained little attention from surgeons in comparison with other types of abdominal wall hernias (inguinal, postoperative)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 11 publications
(27 reference statements)
4
41
0
3
Order By: Relevance
“…Although obesity and larger defects have not generally been found to be related to recurrence [16,17], some authors have accused higher BMI and larger defects to be factors for recurrence after umbilical hernia repairs [18,19]. In the present series, it was not possible to analyze these two factors regarding recurrence.…”
Section: Discussionmentioning
confidence: 81%
“…Although obesity and larger defects have not generally been found to be related to recurrence [16,17], some authors have accused higher BMI and larger defects to be factors for recurrence after umbilical hernia repairs [18,19]. In the present series, it was not possible to analyze these two factors regarding recurrence.…”
Section: Discussionmentioning
confidence: 81%
“…Surprisingly, few studies have addressed the long-term results after the procedure. Short and medium follow-up term retrospective series have, however, shown that the recurrence rates after suture-based repairs in many cases are disappointingly high [2], ranging from 8-9 % [3,4] to a soaring 54 % [5]. These results have lead to the today widespread routine use of mesh reinforcement of all AUH, without any consideration, for example, of the size of the defect.…”
Section: Introductionmentioning
confidence: 97%
“…Obesity and excessive weight gain following repair are obviously potential risk factors. The patient's BMI >30 kg/m 2 and defects >2 cm have been reported as possible factors for surgical failure (45). Moreover, smoking may create a risk for recurrence (46).…”
Section: Factors Influencing Recurrencementioning
confidence: 99%